2017
DOI: 10.1088/2053-1591/aa7b3d
|View full text |Cite
|
Sign up to set email alerts
|

Optically controlled polarization in highly oriented ferroelectric thin films

Abstract: The out-of-plane and in-plane polarization of (Pb 0.6 Li 0.2 Bi 0.2 )(Zr 0.2 Ti 0.8 )O 3 (PLBZT) thin film has studied in the dark and under illumination of a weak light source of a comparable bandgap. A highly oriented PLBZT thin film was grown on LaNiO 3 (LNO)/LaAlO 3 (LAO) substrate by pulsed laser deposition system which illustrates well-saturated polarization and its significant enhancement under illumination of light. We have employed two configurations for polarization characterization; first deals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…Nevertheless, it is difficult to distinguish between the two based on the macroscopic measurements, the fact that sample is polarized under light can be unambiguously accepted. Interestingly, the light‐dependent increase in remnant polarization in KNN‐BNNO is analogous to observations in a few recent studies but is not commonly observed in ferroelectrics . Remnant polarization decreases on exposure to ultraviolet light in classical ferroelectrics such as (Pb,La)(Zr,Ti)O 3 .…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, it is difficult to distinguish between the two based on the macroscopic measurements, the fact that sample is polarized under light can be unambiguously accepted. Interestingly, the light‐dependent increase in remnant polarization in KNN‐BNNO is analogous to observations in a few recent studies but is not commonly observed in ferroelectrics . Remnant polarization decreases on exposure to ultraviolet light in classical ferroelectrics such as (Pb,La)(Zr,Ti)O 3 .…”
Section: Resultssupporting
confidence: 83%
“…It is to be noted that the photovoltaic effect in ferroelectrics is well known since the 1960s and has been investigated for the optical reading of ferroelectric random‐access memories, photodiodes, and photovoltaic applications. Current research is focused on developing band‐gap tuned ferroelectric materials as their performance is restricted by low mobility of charge carriers and short diffusion lengths . Band‐gap tuned ferroelectric materials are capable of hosting multiple functionalities (due to ferroelectricity and semiconducting features), which suggest the possibilities of multiple energy conversions (piezoelectric, pyroelectric, and photovoltaic) simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of free charge generation by light, the sample becomes leakier FE with apparent increase in the both FE polarization and FE coercive force ( figure 1(b)). The observed light-induced change in the ferroelectric loop largely exceeds in magnitude all previous observations [29,[32][33][34]. The corresponding voltampere characteristics further illustrate the photoinduced change in electric properties ( figure 1(b)).…”
Section: Resultssupporting
confidence: 63%
“…Alternatively, light can also generate nonequilibrium carriers by usual band‐band transition, resulting in the electronic effects in ferroelectrics. It has been reported that the free energy of photon‐excited nonequilibrium carriers modifies the thermodynamic behavior of ferroelectric materials, resulting in a lower Curie temperature and narrowed temperature hysteresis of first‐order ferroelectric phase transition; Illumination can also effectively modify the magnitude of the spontaneous polarization, for example, enhancing the value in (Pb 0.6 Li 0.2 Bi 0.2 )(Zr 0.2 Ti 0.8 )O 3 while depressing the switchable polarization in Pb(Zr, Ti)O 3 thin films . However, in all these reported electronic effects the direction of the ferroelectric polarization was not switched solely by light illumination.…”
mentioning
confidence: 99%